Voltammetric selectivity conferred by the modification of electrodes using conductive porous layers or films: The oxidation of dopamine on glassy carbon electrodes modified with multiwalled carbon nanotubes - Henstridge, M; Dickinson, E; Aslanoglu, M; Batchelor-McAuley, C; Compton, R (2010)
Amperometric detection provides a highly sensitive approach to the electroanalytical determination of many target molecules and is widely used in the laboratory and field as well as in the form of disposable sensors. However, the approach can occasionally be restricted by limitations of selectivity; various species present in the target medium may oxidise or reduce at similar potentials. We show that the use of conducting porous layers on the surface of electrodes can be used to modify the mass transport regime from linear (planar) diffusion to one of approximately 'thin layer' character and that this alteration can in favourable circumstances facilitate the amperometric discrimination between species which oxidise or reduce at similar potentials under planar diffusion conditions. The method is illustrated with respect to the detection of dopamine at naked glassy carbon electrodes and at such electrodes modified with a layer of multiwalled carbon nanotubes, and experiments are reported which are consistent with the proposed strategy. The literature for the electroanalytical amperometric detection of dopamine in the presence of interfering molecules such as uric acid, serotonin and ascorbic acid, which often are found to oxidise at potentials close to dopamine, is reviewed and the modus operandi for many chemically modified electrodes apparently designed for the sought resolution of dopamine from these species are found to possibly rely on the physical mechanism proposed. © 2009 Elsevier B.V. All rights reserved.